"A contemporary description of staphylococcus aureus prosthetic valve endocarditis. Differences according to the time elapsed from surgery". Issue 35 (August 2019) - Sáez, Carmen; Sarriá, Cristina; Vilacosta, Isidre; Olmos, Carmen; López, Javier; García-Granja, Pablo Elpidio; Fernández, Cristina; de las Cuevas, Carmen; Reyes, Guillermo; Domínguez, Lourdes; San Román, Jose Alberto
Abstract : Abstract: Staphylococcus aureus prosthetic valve endocarditis (SAPVE) has a poor prognosis. There are no large series that accurately describe this entity. This is a retrospective observational study on a prospective cohort from 3 Spanish reference hospitals for cardiac surgery, including 78 definitive episodes of left SAPVE between 1996 and 2016. Fifty percent had a Charlson Index score >5; 53% were health care-related. Twenty percent did not present fever. Complications at diagnosis included: severe heart failure (HF, 29%), septic shock (SS, 17.9%), central nervous system abnormalities (19%), septic metastasis (4%). Hemorrhagic stroke was not higher in anticoagulated patients. Twenty-seven percent were methicilin-resistant SA (MRSA). Fifteen of 31 had positive valve culture; it was related to surgery within first 24 hours. At diagnosis, 69% had vegetation (>10 mm in 75%), 21.8% perianular extension, and 20% prosthetic dehiscence. Forty-eight percent had persistent bacteremia, related to nonsurgical treatment. Perianular extension progressed in 18%. Surgery was performed in 35 episodes (12 with stroke). Eleven uncomplicated episodes were managed with medical therapy, 8 survived. In-hospital mortality was 55%, higher in episodes with hemorrhagic stroke (77.8% vs 52.2%, odds ratio 3.2 [0.62–16.55]). Early SAPVE was nosocomial (92%), presented as severe HF (54%), patients were diagnosed and operated on early, 38% died. In intermediate SAPVE (9 weeks–1 year) diagnosis was delayed (24%), patients presented with constitutional syndrome (18%), renal failure (41%), and underwent surgery >72 hours after indication; 53% died. Late SAPVE (>1 year) was related with health care, diagnosis delay, and 60% of deceases. Left SA PVE frequently affected patients with comorbidity and health care contact. Complications at diagnosis and absence of fever were frequent. Presence of MRSA was high. Positive valve culture was related to early surgery. Paravalvular extension was frequent; vegetations were large, but its absence at diagnosis was common. Some uncomplicated SAPVE episodes were safety treated with medical therapy. Surgery was feasible in patients with stroke. Mortality was high. There were differences in some clinical characteristics and in evolution according to the time elapsed from valve replacement. Prognosis was better in early SAPVE.